The Quality Evaluation of Air Vacuum Cleaner Attached to The Compressed Air System in Workshop - Panich, Parinya; Wangprasert, Prawit; Mooskopas, Koson; Thongkup, Weraphol; Wangworawong, Wisan; Masika, Sompol (Princess of Naradhiwas University Journal, 2019)
The purposes of this research were to build and evaluate the prototype of the air vacuum cleaner qualities for cleaning the small scraps left over from the process of cutting, filing or drilling in the workshop. The Venturi’s theory was applied to design and build this machine. The recycled plastic container and some wastes from the workshop were used as the materials for machine building. The machine was connected to the compressed air pipe at the workshop. The compressed air was flowed to the machine through the copper pipe which was paralleled throughout the suction pipe length. The cupper pipe was curved to connect to almost the end of suction pipe. The vacuum was occurred at the end of suction pipe and the scraps were sucked to plastic container and the air was released through the plastic container cover. 3 types of scraps was used to determine the suction ability of the machine at 4 bar of compressed air. It was found that the machine was able to suck the coarse sand within 31.32 seconds which was faster than scrap glass and scrap chip, respectively. The satisfaction of machine was evaluated by six working experts in the aspects of design and structure, material selection, machine qualities and overall satisfaction. The average of overall satisfaction score was 4.59 which showed the air vacuum cleaner prototype had a good - very good quality.